Determinants of Foreign Direct Investment : Evidence from Malaysia - Tan, Kah Chun (2011)
The aim of this paper is to examine and explore the determinants influencing Foreign Direct Investment (FDI) inflows into Malaysia. The period under study is 40 years, covering from year 1970 to 2009. Drawing upon existing literature on FDI, some findings on both developed and developing countries in earlier empirical works are investigated for Malaysia. From a host country‟s policy point of view, the study suggests that increase in GDP per capita (market size), infrastructure development, trade openness and economic growth would promote growth. On the other hand, the appreciation of host currency, capital flight and balance of payment surpluses appear to discourage FDI from flowing into Malaysia. This paper also takes into account of the effects of three additional categorical variables, which include the Asian financial crisis, the subprime mortgage crisis and China‟s accession into World Trade Organization (WTO).